Global market inefficiencies - Bartram, Söhnke M.; Grinblatt, Mark (Journal of Financial Economics, 2021)
Using point-in-time accounting data, we estimate monthly fair values of 25,000+ stocks from 36 countries. A trading strategy based on deviations from fair value earns significant risk-adjusted returns (“alpha”) in most regions, especially Asia-Pacific, that are unrelated to known anomalies. The strategy's 40–70 basis point per month alpha difference between emerging and developed markets contrast with prior research findings. A country's pre-transaction cost alpha is positively related to its trading costs, but exceeds country-specific institutional trading costs. Thus, global equity markets are inefficient, particularly in countries with quantifiable market frictions, like trading costs, that deter arbitrageurs.